2017
DOI: 10.1063/1.5011361
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of contact angles at room temperature in high magnetic field

Abstract: The contact angle (CA) goniometer adaptable to a superconducting magnet was developed based on the sessile drop method. The goniometer mainly consisted of the sampling system, the supporting system, and the image acquisition system. Some improvements were taken to avoid the effects of the magnetic field (MF) on the CA measurement. As an example, the CAs of water on two substrates of silica and polymethyl methacrylate (PMMA) were measured using the goniometer. The results with and without a MF showed a good rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The present case is similar to the contact angle measurements of inorganic liquids in a SMF. 20 Thus, the magnetic force does not significantly contribute to the change in the contact angle.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The present case is similar to the contact angle measurements of inorganic liquids in a SMF. 20 Thus, the magnetic force does not significantly contribute to the change in the contact angle.…”
Section: Resultsmentioning
confidence: 97%
“…The SMF intensity can be adjusted from 0 to 8 T. Details of the experimental setup were depicted elsewhere. 20 The contact angle was determined from the droplet profile using the software ImageJ with the plugin "dropsnake". The plugin was programmed using the spline snake approach developed by Stalder et al; 21 it is designed to determine the contact angles at the left and right sides of an asymmetrical drop.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have unique effects on many systems, especially the effect of the Lorentz force on charged ions and the effect of magnetic dipoles on the interfacial interaction . Recent studies have found that magnetic fields alter water contact angles. Ren and Dueñas et al found that a static magnetic field reduced the contact angle of water, which probably stemmed from the change of surface tension in the magnetic field. Yin et al reported that the contact angle of water can increase in a simulated microgravity environment generated by a large gradient magnetic field.…”
Section: Introductionmentioning
confidence: 99%